RANCANGAN BAHAN AJAR MATEMATIKA BERBASIS MOTIF BATIK MELAYU RIAU PADA MATERI TRANSFORMASI GEOMETRI KELAS IX SMP/MTs - Leliyana Nurqolbi; Yenita Roza; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is importance of teaching materials that inroduced regional culture in learning process as an effort to preserve culture. This research aims to produce a design of mathematics teaching materials that introduce regional culture to students by introducing the Riau Malay Batik Motive. This research is the beginning part of the development of mathematics teaching by using the ADDIE model that consists of Analysis, Design, Develop, Implementation, and Evaluation. Reasearch and development (R&D) conducted by researchers has reached the design stage.Key Words: Mathematics Teaching Materials, Riau Malay Batik Motive, ADDIE Model.